From urban sprawl to concentrated urban development? A multidimensional stocktaking of suburbanisation - Adam, Brigitte (Raumforschung und Raumordnung | Spatial Research and Planning, 2019)
In view of a phase of reurbanisation of German large cities, in this paper the question is raised, whether, where, with which intensity and tendency suburbanisation still can be found. Answers will be delivered by a multidimensional quantitative model. In addition to the population development, which often indicates a reurbanisation or suburbanisation trend, it includes the labour market and land consumption. Going beyond city-hinterland relations, it is investigated whether the surrounding areas of large cities show a development according to the ideal of decentralised concentration – in particular a concentration on medium-sized cities – or whether the development is more dispersely spread over smaller towns and municipalities. The calculations lead to a suburbanisation index, which can be periodically produced every few years (monitoring). Beyond a perspective mainly orientated towards the population development, the suburbanisation idea is improved and completed. Comparing the various dimensions (population, labour market, land consumption) generates partly controversial results.
Keywords: Suburbanisation; Reurbanisation; Index; Population development; Labour markets; Land consumption